A Simple Rule for Judging Compliance Using Highly Censored Samples - Hau, Ian; Berthouex, Paul M. (My University, 1991)
A special case of judging compliance is when the effluent limit is set at a level below the method limit of detection (MDL) of the substance being monitored. In many such cases, almost all measurements on the effluent are reported as "not detected." A simple rule is proposed for judging compliance of the effluent in this situation. It makes allowance for random errors in measurements on the effluent and it recognizes that an effluent can be in compliance and still produce a proportion of values above the MDL.